Optimalisasi Laporan Keuangan dan Pajak Pada Lembah Patih Living Space & Eatery Purwokerto - Permatasari, Santi; Setiyawan, Hendra; Isfanza, Nurmalita; Natalia, Helfi; Nugrahaningtyas, Ardila; Rafinda, Ascaryan (Journal of Community Service and Society Empowerment, 2024)
Lembah Patih Living Space & Eatery as one of the places to eat or café located in Baturraden District, Banyumas Regency. The location of Lembah Patih is close to several tourist attractions in Baturraden. This strategic position is an opportunity for the surrounding community to develop businesses, and improve existing MSMEs. Through the optimization of financial and tax reports at Lembah Patih Living Space & Eatery Purwokerto, it is hoped that it can provide an understanding to Patih Valley stakeholders to optimize Patih Valley's business processes through financial recording procedures, and increase awareness and understanding related to calculating and reporting MSME taxes. The implementation of this community service activity is carried out through three stages, namely the planning, implementation, and evaluation stages. The main problems faced by Lembah Patih are recording financial statements that are not in accordance with accounting standards, recording Patih Valley assets that have not been implemented, and Patih Valley tax reporting that has not been implemented. Based on the problems that have been identified in partners, the community service team determines solutions or alternatives to optimize Lembah Patih's business processes by providing and explaining standard and simple financial report formats for Lembah Patih to try to implement, providing and explaining standard and simple asset recording formats, and providing ways to calculate MSME taxes and MSME tax reporting procedures. The implications of this community service implementation process are expected to be implemented by Lembah Patih gradually for the development of Lembah Patih Living Space & Eatery Purwokerto.